Against Irish Modernism: Towards an Analysis of Experimental Irish Poetry. Issue 1 (May 2016) - Hutton-Williams, Francis
Abstract : This essay rewrites the history of Irish poetic experiment away from modernism, or at least from contemporary industry-driven senses of the term which have multiplied to the point of overuse as a catch-all category. It is divided into two parts. The first part of the essay focuses on questions of literary history, defining some of the key trends of literary production and reception in Ireland during the 1920s and 30s. By surveying the negative impact of religion and censorship on literary development within the Irish Free State (1922–1937), the essay challenges the concept of Ireland as a place of widespread modernist assertion. The second part of the essay steers the discussion towards an 'avant-garde' trio of Irish writers, offering an extended and detailed characterisation of their poetry. It traces the emergence of an experimental Irish poetry with a selection of examples taken from Denis Devlin's Intercessions (1937), Thomas McGreevy's Poems (1934) and Samuel Beckett's Echo's Bones and Other Precipitates (1935), showing how poetic experiments of the 1930s challenge the lyric as a versifying form after Irish independence.